PREDIKSI KINERJA KEUANGAN PERUSAHAAN ASURANSI SYARIAH MENGGUNAKAN METODE ARIMA, EXPONENTIAL SMOOTHING, DAN HYBRID - Devita Apriliani; Nina Fitriyati; Dhea Urfina Zulkifli (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Insurance is a contract made by an insurance company with a policy holder. One way to assess the stability of company is its financial performance. The aim of this study is to predict the financial performance of sharia insurance company using two factors, namely ROA (Return on Assets) and ROE (Return on Equity). The secondary data used in this research is derived from the quarterly financial reports of an Islamic insurance company from the year 2013 to 2022. The study used ARIMA (Autoregressive Integrated Moving Average), Exponential Smoothing (ETS), and Hybrid methods. The results showed that the ARIMA model is the best way to better predict both ROA and ROE. Compared to other methods that have been evaluated, the ARIMA model showed more accurate results in predicting financial  performance measured through ROAs and ROEs. Predictions show that the ROA value is relatively stable, indicating that the company is efficient in managing resouces while the ROE value tends to fail, which indicates that the identified company is less good at delivering returns to shareholders. Therefore, it can be one of considerations for people who wants to buy insurance or invest